2018
DOI: 10.1016/j.ijimpeng.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of global stiffness and equivalent model on prediction of impact response of RC beams

Abstract: A spring-mass model is commonly used to predict the impact response of a beam. This type of models usually assumes the beam response is governed by flexural and/or shear response mode in deriving the equivalent structural parameters, i.e. equivalent stiffness and mass. However, it is also well-known that under high-speed impact the response during the impact could be limited to a localized area around the impact point. For such cases, the equivalent stiffness and mass estimated from the global response of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…In addition, there are some limitations in predicting the transient impact response of RC beams, especially the stress wave propagation. Based on their studies, Pham and Hao [19] and Yi et al [20] suggested that the impact-induced wave propagation should be taken into account in the local response phase.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are some limitations in predicting the transient impact response of RC beams, especially the stress wave propagation. Based on their studies, Pham and Hao [19] and Yi et al [20] suggested that the impact-induced wave propagation should be taken into account in the local response phase.…”
Section: Introductionmentioning
confidence: 99%
“…t 1 represents the instant of maximum impact force as mentioned above. t 1 1 , t 3 1 , t 5 1 represent the instant of 0.1, 0.3, and 0.5 ms after the maximum impact force, respectively. The length of the vector represents the magnitude of acceleration.…”
Section: Response Of Force and Midspan Deflectionmentioning
confidence: 99%
“…It is proved that the behavior of beams has improvement with the increase of reinforcement ratio. Pham et al [5] changed the beam span to investigate the influence of global stiffness on the response of RC beams. It is found that the behavior of RC beams during the first impact impulse was almost constant, but the displacement, failure mode, and reaction at later stages are changed.…”
Section: Introductionmentioning
confidence: 99%
“…As the crucial part of the rear axle, the condition of the main reducer has a direct impact on the level of vibration, safety and comfort, and any fault of the main reducer may lead to production downtime, economic loss and human injury [1,2]. Vibration signals generated during the running process can effectively reflect the variance of condition.…”
Section: Introductionmentioning
confidence: 99%